A theoretical analysis of season length restrictions in fisheries management. Issue 4 (2002) - Xu, Qing; Batabyal, Amitrajeet A.
Abstract : This paper studies season length restrictions in fisheries management from an ecological-economic perspective. We first construct a model of a stylized fishery in which season length restrictions are used to manage the fishery. We then show how the dynamic and the stochastic properties of this fishery can be used to construct two managerial criteria that are meaningful from an ecological standpoint. Finally, using these two criteria, we discuss a probabilistic approach to fisheries management in which the principal focus of a manager is on moving the fishery away from the least desirable state of existence.